Kondisi Sosial Ekonomi Masyarakat Korban Bencana Lumpur Lapindo Pada Kawasan Permukiman Di Desa Panggreh - Oktafiana Wahyu P; Moch Shofwan (LPPM Universitas Putera Batam, 2023)
May 29 2006 is the day when the Lapindo Mud disaster occurred in Sidoarjo Regency. This natural disaster is a disaster where the ground releases gas along with hot mud with a temperature of 100 degrees Celsius. The Lapindo Mud disaster has inundated several villages located in several sub-districts in Sidoarjo Regency, where until now the condition of hot mudflow around the center of the eruption is still increasing. The village of Panggreh, situated in the Jabon District, Sidoarjo Regency, serves as a resettlement area for the victims of the Lapindo Mudflow. The region has a settlement where a portion of the Lapindo mudflow disaster victims have been relocated. The objective of this study is to comprehend the socio-economic situation of the Lapindo Mud Disaster victims in Panggreh Village. This research applies primary and secondary data collection methods along with descriptive qualitative research methodology that uses photo mapping techniques. The study's findings reveal that the educational facilities in Panggreh Lengap village are in excellent condition, the buildings were still sturdy and very decent, the educational services were very good. Health facilities and services are also good. The economy of the middle to lower class community. The majority of people feel the negative impact of moving their residence because of the Lapindo.